2017
DOI: 10.4067/s0717-95022017000200049
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Morphological Characteristics During the Period 2005 ­ 2014 in a Sample of Serbian 7 - Year-Old Children

Abstract: Morphological characteristics of children commonly imply the processes of growth and development. Information on children's growth in height and their body weight is often used as the indicator of the children's health and nutritional status. As the parameters are changeable both temporally and spatially, it is important to provide their continual assessment. The aim of the study is to investigate the changes in morphological characteristics in a sample of Serbian 7-year-old children in the period 2005-2014. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
1
3
0
1
Order By: Relevance
“…Among 1134 children (age 7–12 years) studied in 2012, 18.9% were overweight, which is very similar to our observed overweight rate of 16% [ 23 ]. From 2010 to 2014, the heights and weights of Serbian school children ( n = 671) were reported to be somewhat lower than in our cohort, with 15.3 kg/m 2 being the average BMI for boys, similar to our observation, while for girls, they reported 14.7 kg/m 2 , which was slightly lower than our observation of 15.8 ± 2.3 kg/m 2 [ 24 ]. Although the body fat percentage calculated from skinfolds was somewhat higher than that observed in the CHOP study in 6-year-old children (girls 16.4 ± 4.6%, boys 14.8 ± 5.1%), findings agreed that there were no significant differences between study groups, while values were significantly higher for girls than for boys [ 25 ].…”
Section: Discussionsupporting
confidence: 80%
“…Among 1134 children (age 7–12 years) studied in 2012, 18.9% were overweight, which is very similar to our observed overweight rate of 16% [ 23 ]. From 2010 to 2014, the heights and weights of Serbian school children ( n = 671) were reported to be somewhat lower than in our cohort, with 15.3 kg/m 2 being the average BMI for boys, similar to our observation, while for girls, they reported 14.7 kg/m 2 , which was slightly lower than our observation of 15.8 ± 2.3 kg/m 2 [ 24 ]. Although the body fat percentage calculated from skinfolds was somewhat higher than that observed in the CHOP study in 6-year-old children (girls 16.4 ± 4.6%, boys 14.8 ± 5.1%), findings agreed that there were no significant differences between study groups, while values were significantly higher for girls than for boys [ 25 ].…”
Section: Discussionsupporting
confidence: 80%
“…One study conducted by Fu et al [11] showed that there are positive secular trends in height which is higher during the onset of puberty and then dramatically decreased during the middle and end of puberty (after age 12 years). A number of studies have also analyzed the trends in height at certain ages [8], [11], [12], [19], [20], [21], [22]. Compared with boys and girls of our study in the same age indicated a lower average height of our samples than those of previous studies, as well as when compared to Turkish children aged 6-17 years [23] and Italian children aged 9-10 years [24].…”
Section: Discussionmentioning
confidence: 40%
“…The aforementioned method is used to establish the nutritional status of children and adolescents, which represents one of the most important indicators of health, psychophysical abilities and the potential for normal growth and development (Stamenkovič, Bratić, Berić, & Pantelić, 2017). Thus, it can function as a prognostic factor of their state of health (Marković, Igrutinović, Kostić, & Vuletić, 2008;Pavlica, Rakić, & Sironjić, 2017). Any greater deviations from optimal body mass values are indicators of symptoms of a health disorder, or indicators of a preexisting condition (Vlaški & Katanić, 2010).…”
Section: Introductionmentioning
confidence: 99%